EVALUASI SISTEM JARINGAN DRAINASE DI JALAN SOEKARNO HATTA MALANG - Blasius Lobe Mato; Suhudi Suhudi (Universitas Tribhuwana Tunggadewi, 2012)
Pond that happened in Soekarno Hatta Street Malang City reached height of ± 30 cm and duration of the pond was ± 25 minutes. This condition resulted in broken traffic band and people took a longer other band. One of the generated impact of the existence of the pond was the damage on hard surface of the street. The final goal of this activity was in order that drainage network system can perform well in a long time according to the plan so that it can endure evaluated from construction facet and its function. The method used was by analysing flood discharge that happened (Qa) 2,710 m3/s and channel capacity existing (Qke) 2,433 m3/s, hereinafter evaluated and its result was that the existing channel is unable to conduct water well. The evaluation of channel capacity in handling the problem of flood can be conducted by dimension repeat channel. Dimension of channel plan in the form of square made from concrete coat with the width of channel base is (b) 1,10 m and the height of water surface is (h) 0,65 m, obtained plan channel capacity (Qkr) 2,895 m3/s. Final result of analysis showed Qa < Qkr, the flood will not happen and capacity control (∆Q) = 6,8%